Evaluation of commercially available polylactic acid (PLA) filaments for 3D printing applications - Matos, Bruna Driussi Mistro; Rocha, Valmir; da Silva, Eraldo Jannone; Moro, Franco Henrique; Bottene, Alex Camilli; Ribeiro, Clovis Augusto [UNESP]; dos Santos Dias, Diogenes [UNESP]; Antonio, Selma Gutierrez [UNESP]; do Amaral, André Capaldo; Cruz, Sandra Andrea; de Oliveira Barud, Helida Gomes; Silva Barud, Hernane da (Springer Nature, 2019)
Polylactic acid (PLA) is a biodegradable and bioresorbable biopolymer that has successfully been applied in biomedical and related fields. It is in the form of filaments, presenting different colors, with the purpose to be used in the three-dimensional printing (3D) technique. Thus, this work aimed to characterize five commercially available PLA filaments which were differentiated by color, as follows: blue (1), gray (2), transparent (3), orange (4) and natural (5) comparing to a pellet pattern. Thermal characterization was performed throughout simultaneous thermogravimetry (TG), derivative thermogravimetry (DTG), differential thermal analysis (DTA) and differential scanning calorimetry (DSC). Significant differences in the enthalpies and temperatures of crystallization and melting indicated differences in crystallinity of the filaments corroborated by the XRD analysis. While analyzing using TG/DTG–DTA, significant differences in thermal stability were observed. The absorption spectroscopy in the infrared was also done to determine the chemical composition of the samples. Additionally, it was also observed the structure, size and roughness of the filaments using confocal microscopy building three-dimensional images. The oscillatory rheometer was employed to determinate the complex viscosity (η∗), the store modulus (G′) and the loss modulus (G′ ′) as a function of frequency (ω). After conducting the characterizations, it was possible to compare the five types of PLA filaments and identify the best one to feature a functionalization in the future, which possibly enable them in tissue engineering applications. Results indicated that the blue filament fulfilled the best results regarding print quality, higher-temperature degradation and thermal stability, with the molar mass and viscosity superior to the other filaments.
Keywords: Confocal microscopy; FTIR spectra; PLA filaments; Rheological analysis; Thermal stability; XRD